Does Female Stock Labor Promote Economic Growth? A Case of Pakistan - Ali, Kousar; Sami, Dr. Fariha; Arafat, Yasir (Journal of Business & Tourism, 2024)
This study investigates the significant contribution of the female workforce to the economic growth of Pakistan for the time 1988 - 2022. Various methodological tests are employed to determine the integration levels of the study’s variables. Subsequent diagnostic tests are conducted to assess autocorrelation and heteroscedasticity, ensuring adherence to the assumptions of classical linear regression. Given the mixed order of integration of variables, the Autoregressive Distributive Lag Model (ARDL) is applied for both long-run and short-run estimations. The findings indicate a positive impact of female capital stock on Pakistan’s economic growth. Furthermore, the Multivariate Granger Causality test establishes a one-way causal relationship, demonstrating the influence of the female stock of capital on the economic growth of Pakistan. In conclusion, the study advocates for creating ample opportunities for women in Pakistan to unlock the full potential of the economy.